2018
DOI: 10.1159/000490167
|View full text |Cite|
|
Sign up to set email alerts
|

LINC01121 Inhibits Cell Apoptosis While Facilitating Proliferation, Migration, and Invasion Though Negative Regulation of the Camp/PKA Signaling Pathway via GLP1R

Abstract: Background/Aims: Pancreatic cancer is an aggressive malignancy as a result of highly metastatic potential. The current study was carried out to alter the expression of LINC01121 in pancreatic cancer, with the aim of elucidating its effects on the biological processes of cell proliferation, migration, invasion, and apoptosis. We hypothesized that both the GLP1R gene and cAMP/PKA signaling pathway participate in the aforementioned process. Methods: Microarray data (GSE14245, GSE27890 and GSE16515) and annotating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…These results indicated that LINC01121 acts as an oncogene and is involved in the process of breast cancer proliferation, migration, and invasion. Qian et al 10 reported that LINC01121 is overexpressed and acts as an oncogene in pancreatic cancer tissues, which is similar to our results. One of the functions of lncRNAs is to act as miRNA sponges to regulate the expression of their miRNA targets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that LINC01121 acts as an oncogene and is involved in the process of breast cancer proliferation, migration, and invasion. Qian et al 10 reported that LINC01121 is overexpressed and acts as an oncogene in pancreatic cancer tissues, which is similar to our results. One of the functions of lncRNAs is to act as miRNA sponges to regulate the expression of their miRNA targets.…”
Section: Discussionsupporting
confidence: 92%
“…LINC01121 has been reported to be aberrantly expressed and act as an oncogene in pancreatic cancer. 10 Huang et al 11 reported that pterostilbene could suppress proliferation and epithelial-to-mesenchymal transition and promote apoptosis in breast cancer cells. Further investigation showed that pterostilbene can decrease the expression of LINC01121, suggesting that LINC01121 may act as an oncogene in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study also demonstrated decreased expression of the lncRNAs LINC01121, PTTG3P and HOTAIR following pterostilbene treatment. In pancreatic cancer, LINC01121 is shown to inhibit cell apoptosis and promote cell proliferation, migration and invasion via interaction of GLP1R in the control of the Camp/PKA signaling pathway (37). In hepatocellular carcinoma, enforced expression of the lncRNA PTTG3P facilitates cell proliferation, invasion, migration, and metastasis via activation of the PI3K/Akt pathway (38).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (LncRNAs) are transcripts with length of at least 200 nucleotides featuring limited protein-coding capability and poorly conserved sequence among mammalian species, and they account for about 98% of transcripts in human genome [4]. LncRNA has been reported to be involved in various biological behaviors, such as the regulation of cell proliferation, apoptosis, autophagy and migration [5][6][7][8]. Some lncRNAs are reported to involve in the modulation of maintain normal tissue structure and permeability [9][10][11].…”
Section: Introductionmentioning
confidence: 99%